1989
DOI: 10.1161/01.str.20.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indomethacin and a free radical scavenger on cerebral blood flow and edema after cerebral artery occlusion in cats.

Abstract: Using the middle cerebral artery occlusion model in cats, we evaluated the possible role of the cyclooxygenase pathway in alterations of local cerebral blood flow and the development of cortical edema following prolonged ischemia or recirculation. We divided 57 cats into three groups, and each cat received saline (control), indomethacin, or the free radical scavenger ONO-3144. Each group was subdivided into prolonged ischemia (4 hours of occlusion: PI) and recirculation (2 hours of occlusion followed by 2 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Consequently, these studies have led to contradictory findings. Some investigators found that COX inhibition ameliorates ischemic injury, whereas others reported no effect or worsening of the damage (Cole et al, 1993;Johshita et al, 1989;Petersen, 1989). The results of the present study, in concert with recent data in COX-2-null mice (Iadecola et al, 2001), help reconcile these conflicting observations.…”
Section: Cox-1 and Ischemic Injury 1439supporting
confidence: 58%
“…Consequently, these studies have led to contradictory findings. Some investigators found that COX inhibition ameliorates ischemic injury, whereas others reported no effect or worsening of the damage (Cole et al, 1993;Johshita et al, 1989;Petersen, 1989). The results of the present study, in concert with recent data in COX-2-null mice (Iadecola et al, 2001), help reconcile these conflicting observations.…”
Section: Cox-1 and Ischemic Injury 1439supporting
confidence: 58%
“…In addition, previous studies have reported the effect of nonselective COX inhibitors, e.g., indomethacin and ibuprofen, on cerebral ischemic damage. The results of these investigations have been contradictory; some report protection and others show no effect or worsening (Harris et al, 1982;Johshita et al, 1989;Cole et al, 1993). These conflicting observations are likely to result from the fact that the effects of COX-2 inhibition were confounded by effects of COX-1 inhibition, an enzyme involved in normal cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, indomethacin, one of the agents studied most extensively, has profound effects on cerebral blood flow and vascular reactivity (for review, see Busija and Heistad, 1984). Because indomethacin was administered before or shortly after induction of ischemia (Harris et al, 1982;Johshita et al, 1989), it is likely that the attendant cerebrovascular effects of this agent influenced the outcome of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the nizofenone administration, the cortical PO 2 level was higher than the preocclusion one, and the brain edema was not prevented. One of the causes of brain edema formation was reported to be the superoxide production induced by the excessive supply of O 2 after the start of reperfusion [17,18]. Accordingly, the effect of nizofenon on the cerebral blood flow may be inconvenient effect, at least on the edema.…”
Section: Discussionmentioning
confidence: 99%